ANALYSIS OF PROFITABILITY DETERMINANTS IN ISLAMIC BANKS IN INDONESIA AND MALAYSIA - Husen Sobana, Dadang; Fuji Hakiki, Muhamad; Ibrahim, Asep Warsa (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
The Islamic banking sector in Indonesia and Malaysia has grown significantly, with Islamic banks operating under Sharia principles, differing from conventional banks in business models and risk management. This study analyzes the impact of income diversification, capital adequacy, asset quality, operational efficiency, and liquidity on the profitability of Islamic banks, using secondary data from the annual financial reports of 20 Islamic banks from 2019–2023. The variables examined include Return on Assets (ROA), income diversification (DIV), capital adequacy ratio (CAR), non-performing financing (NPF), operational efficiency (BOPO), and liquidity. The findings show that income diversification, capital adequacy, operational efficiency, and the financing-to-deposit ratio (FDR) significantly impact profitability. However, the NPF ratio shows a negative but statistically insignificant effect on profitability, likely due to effective risk management. The FDR ratio has a positive and significant effect, indicating that proper financing allocation enhances profitability. Asset quality and operational efficiency are identified as the most significant factors affecting Islamic bank profitability in Indonesia and Malaysia. While income diversification, capital adequacy, and liquidity do not show significant effects, they remain important for careful management. This research provides key insights for Islamic bank management in improving profitability by focusing on credit risk and operational efficiency.